The family Gi diet : - Gallop, Rick (Virgin Books Ltd, 2006)
The latest in Rick Gallop's market leading "Gi Diet" series, "The Family Gi Diet" offers individualized weight-loss and healthy eating strategies for every member of the family - whether to help lose weight or simply eat healthy and keep in good shape. No two people have the same body chemistry, nutritional needs and eating habits, so how do you prepare a healthy meal to suit every member of the family? How do you help your overweight child? What can you do about bad eating habits? What if you're pregnant? Does BMI apply to older people? For "The Family Gi Diet" Rick has teamed up with his wife, Dr Ruth Gallop, to address all of these questions and more. With sound advice, practical tips, and fifty new green-light recipes, you'll be well on your way to improving the health of all your loved ones.